Infrastructure of Cultural Leisure in Consumer Society in Student View: Prospects and Problems of Promotion - Baranov, Vladimir V. (2021)
The formation of the cultural leisure infrastructure structures the modern space in a special way and contributes to the formation of a new leisure sphere of modern society. The cultural leisure industry today is not only and not so much a training field, but a huge segment of the country's leisure market. The purpose of the study is to study the features of the cultural leisure infrastructure and its role in the representation of students. Research methods: as a research method, a questionnaire survey was used as a method of collecting primary information, which allows us to identify various aspects related to students' ideas about the ways and problems associated with spending free time. Research results: the article considers the role of leisure in the consumer society. The features of the development of leisure infrastructure are revealed. The novelty and originality of the study lies in the fact that for the first time the field of leisure is considered in the representation of students. It is revealed that leisure time for students is a criterion for identifying the status of a person, acts, as a social marker of a certain lifestyle, is a sphere of manifestation of different capabilities of an individual. It is determined that leisure is often aimed not so much at enjoying free time, as at filling the consumption of non-working time. For the first time, the reasons for the visiting of students in leisure studios are shown. It is revealed that there is a randomness of choice; the desire to find new meanings; a way of searching for oneself. It is shown that students note the leisure industry as a sector where, for a certain fee, the client buys not only the opportunity to spend time, but also new goals and ways of self-expression. It is determined that today leisure studios are not just a place where classes are held twice a week, but also a well-organized recreational space. Leisure studios are organized in such a way that a person who is engaged in, who is interested in it, feels that he belongs to a certain clan. It is revealed that the leisure industry sells not just services, but mood, and it is the leisure studios organized on this principle that are the most successful in the market of leisure services. From the point of view of students, an important role in the leisure industry is played by the teacher, as a guide to the world of hobbies. It is determined that it is the presence of a teacher that structures training in a special way. Practical significance: The data obtained in this work can be used in marketing research, economic sciences, advertising psychology, as well as for further theoretical development of this issue.